A mudança de multicanal para omnichannel em uma empresa atacadista: um estudo de caso - Franco, Renata de Souza (2019)
Competition among supply chain agents to access new revenue streams means that services offered to consumers tend to be expanded. One of the most profound changes was the emergence and consolidation of new service channels, especially the online channel. The growing number of channels increases the complexity of the logistics, as these changes require significant investments in infrastructure, processes and resources for storage and distribution, making logistics even more important for economic agents. As the lines between online and physical channels are becoming increasingly distorted, a new approach to channel integration is evolving, called omnichannel (OC). In theoretical terms, international studies have taken approaches to the evolution to the omnichannel model, focusing on retail companies. No studies were found in the literature on the implementation of the strategy by wholesale companies, or models that consider this transition to business-to-business (B2B) business. Thus, this paper aims to evaluate the omnichannel implementation process in a Brazilian wholesale company, which operates in the B2B model. In this context, we sought to recognize the motivating factors, present the logistics process involved in the sales channel, recognize the organizational structure to meet market demand. In terms of methodological procedures, the research approach can be classified as qualitative, applied in nature. The strategy adopted was the single case study, and the data were obtained through semi-structured interviews with managers and professionals involved in the adoption of the strategy by the company studied. Data analysis showed that the company operates in two segments simultaneously - retail in B2C model and wholesale in B2B model, in well-segregated units. Prior to adopting its unified sales channel strategy, the company transformed its e-commerce model into a repositioning marketplace platform. Unlike what has been observed in the literature, the company's online channel was created simultaneously with its integration with other channels, from the point of view of logistics processes. As a contribution of the work, it was possible to observe how the model transformation strategy was adopted, and to identify the degree of maturity of the company facing the challenge of B2B implementation in the omnichannel model. The study's limitations include the fact that it is a unique case study with few interviews conducted with the employees involved in the strategy. As an agenda for future research, it is suggested that the study be extended to other employees, attackers, and other supply chain agents analyzed: suppliers and customers (small retailers).